2009
DOI: 10.1056/nejmsa0806819
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Trial of Financial Incentives for Smoking Cessation

Abstract: BACKGROUND: Smoking is the leading preventable cause of premature death in the United States. Previous studies of financial incentives for smoking cessation in work settings have not shown that such incentives have significant effects on cessation rates, but these studies have had limited power, and the incentives used may have been insufficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
502
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 767 publications
(517 citation statements)
references
References 18 publications
11
502
1
Order By: Relevance
“…However, we feel that their subsequent discussion, citing the research of Volpp et al [12] and Higgins et al [13], diminishes this statement and provides a misleading view of the value of PFIs in promoting health behaviour once the incentive has ceased. While Volpp et al's [12] randomized controlled trial of PFIs for smoking cessation found significant differences in smoking cessation after the incentive had been removed, the study has three issues that limit its impact. First, there is little detail of the content of the other components of the intervention.…”
Section: Evidence For Long-term Effects Of Incentives On Health Behavmentioning
confidence: 94%
“…However, we feel that their subsequent discussion, citing the research of Volpp et al [12] and Higgins et al [13], diminishes this statement and provides a misleading view of the value of PFIs in promoting health behaviour once the incentive has ceased. While Volpp et al's [12] randomized controlled trial of PFIs for smoking cessation found significant differences in smoking cessation after the incentive had been removed, the study has three issues that limit its impact. First, there is little detail of the content of the other components of the intervention.…”
Section: Evidence For Long-term Effects Of Incentives On Health Behavmentioning
confidence: 94%
“…Financial incentive programmes promote smoking cessation by providing financial incentives to quit. Certain financial incentive programmes have demonstrated their effectiveness over a 1 year horizon 25, 28. The advantage of financial incentive programmes include their ease of implementation by companies and insurance companies.…”
Section: Methodsmentioning
confidence: 99%
“…14 Patient financial incentives have been used successfully to promote other health behaviors influenced by present-biased preferences, 15 such as smoking cessation 16 and weight loss. 17 Financial incentives may be particularly salient for Medicaid beneficiaries.…”
Section: Introductionmentioning
confidence: 99%